"But What About Real Mental Illnesses?" Alternatives to the Disease Model Approach to "Schizophrenia". (January 2018) - Cooke, Anne; Kinderman, Peter
The old dichotomy between "neurosis" and "psychosis" appears to be alive and well in the debate about psychiatric diagnosis. It is often suggested that while diagnostic alternatives may be appropriate for the relatively common forms of distress with which we can all identify such as anxiety and depression, psychiatric diagnoses remain vital for experiences such as hearing voices, holding beliefs that others find strange, or appearing out of touch with reality—experiences that are traditionally thought of as symptoms of psychosis. Such experiences are often assumed to be symptoms of underlying brain pathology or "real mental illnesses" that need to be diagnosed or "excluded" (in the medical sense of ruling out particular explanations of problems) before deciding on the appropriate intervention. This article argues that this belief is misguided, and that far from being essential, psychiatric diagnosis has the potential to be particularly damaging when applied to such experiences. It describes an alternative perspective outlined in a recent consensus report by the British Psychological Society Division of Clinical Psychology ( Understanding Psychosis and Schizophrenia ), which has attracted significant attention in the United Kingdom and internationally. The report argues that even the most severe distress and the most puzzling behavior can often be understood psychologically, and that psychological approaches to helping can be very effective. It exhorts professionals not to insist that people accept any one particular framework of understanding, for example, that their experiences are symptoms of an illness. This article outlines that report's main findings, together with their implications for how professionals can best help.